BRAND LOYALTY OF WORKING WOMEN TOWARDS SKIN CARE PRODUCTS & DEMOGRAPHIC FACTORS AFFECTING IT (WITH REFERENCE TO RAJKOT CITY) - Vandna H. Gurubaxani (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2021)
The main Aim of this paper is to examine working women’s brand loyalty with reference to skin care products as a part of cosmetics in Rajkot city of Gujarat. Moreover the impact of Demographic factors on brand loyalty for skin care products is also analyzed by researchers. For this purpose Questionnaire were distributed among 50 working women respondents which covers student, Business women, Professional and Job category selected by Researchers. Keeping in mind geographical concentration, a convenient sampling technique has been used for this study. Chi-square - Non parametric test is used by researcher apart of Data analysis. Result shows that Majority of working women of Rajkot city are Loyal towards their particular brand of skin care products and there is no relation between Demographic factors and women’s brand loyalty towards skin care products. The study helps also too marketers of cosmetics to frame various policies and strategies regarding product, Price, place (distribution) and promotion apart of the marketing mix.